AB0764 Gender Differences in Axial Spondyloarthritis. (9th June 2015) - Kenar, G.; Can, G.; Cetin, P.; Yarkan, H.; Sari, I.; Birlik, M.; Akkoc, N.; Onen, F.
Abstract : Background: Gender differences in demographic and clinical features of ankylosing spondylitis (AS) has consistently been demonstrated in several cohorts but there is little knowledge of those of axial spondyloarthritis (axSpA) as a whole group and of nonradiographic axial spondyloarthritis (nr-axSpA). Objectives: The aim of this study was to assess the gender differences in axSpA. Methods: Demographic and clinical data in our local axSpA database were evaluated and compared between male and female patients. Subgroup analyses in patients with AS/radiographic axSpA (r-axSpA) and nr-axSpA were also performed. Results: There were 438 patients with axSpA [279 male (64%)], who fulfilled the ASAS classification criteria (Table 1 ). 349 out of them were classified as having AS/r-axSpA [236 male (68%)] and 89 as having nr-axSpA [43 male (48%)]. In female patients with axSpA, age of disease onset and age of diagnosis was older and delay of the diagnosis was longer compared with male patients (p<0.05). Peripheral arthritis and dactilitis were seen more in females (p<0.05) but entesitis was more frequent in males. At the time of diagnosis, BASDAI was higher in females (p<0.05); but BASMI scores (p<0.05) and CRP (p<0.05) were higher in males. Although neck pain was more common in female axSpA patients; cervical rotation disability and BASMI score assessments were worse in males (Table 1 ). When subgroup analysis was performed, females with nr-axSpA were found as having worse BASDAI (p<0.05) and BASFI scores (p<0.05) and males with AS as having higher CRP levels (p<0.05) and worse BASMI scores (p<0.05). Conclusions: This study demonstrated that AS/r-axSpA was more prevalent among men but the prevalence of males and females in patients with nr-axSpA was similar. While subjective disease activity parameters were higher among women with axSpA as well as in those with nr-axSpA, men with axSpA experienced higher objective disease activity parameters and more restricted spinal mobility as well as in those with AS/r-axSpA. However, objective disease activity and spinal mobility scores were similar between women and men with nr-axSpA. Disclosure of Interest: None declared